Development of IoT-controlled irrigation and fertilization system for fertigation farming - Bariman, Norhafzan; Mahmod, Masrul Nizam; Hat, Mohd Kamal (Indonesian Institute for Counseling, Education, and Therapy (IICET), 2024)
This paper presents the development of irrigation and fertilization systems for fertigation farming with IOT control. The irrigation and fertilization method used in this study is drip irrigation. Meanwhile, an IoT system is used to monitor the irrigation and fertilization processes to ensure plant quality. Through this system, users can monitor fertigation plants in terms of water levels, the amount of fertilizer mix in the fertigation tank, and watering times using smartphones. The correct amount of fertilizer mix A and B (depending on the type of plant) will ensure that plants receive sufficient nutrients for growth processes. With the correct fertilizer mix measured using an Electrical Conductivity (EC) meter, nutrients to plants can be supplied at an adequate rate.